Case Report of Haemophilus parainfluenzae Sepsis in a Newborn Infant Following Water Birth and a Review of Literature - Manu Kaushik; Brittany Bober; Leonard Eisenfeld; Naveed Hussain (Thieme Medical Publishers, Inc., 2015)
Abstract Water birth has grown in popularity over the recent years. Although beneficial for mothers, there are concerns for the infants. There are previous reports of infection following water birth. The information regarding infection with Haemophilus parainfluenzae is limited. We report a case of a neonate with H. parainfluenzae bacteremia following water birth. The child was successfully treated with both antibiotic and supportive care. Previous reports of neonatal H. parainfluenzae infection are reviewed.